2017
DOI: 10.5194/angeo-35-777-2017
|View full text |Cite
|
Sign up to set email alerts
|

Tracking patchy pulsating aurora through all-sky images

Abstract: Abstract. Pulsating aurora is frequently observed in the evening and morning sector auroral oval. While the precipitating electrons span a wide range of energies, there is increasing evidence that the shape of pulsating auroral patches is controlled by structures in near-equatorial cold plasma; these patches appear to move with convection, for example. Given the tremendous and rapidly increasing amount of auroral image data from which the velocity of these patches can be inferred, it is timely to develop and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 20 publications
1
38
2
Order By: Relevance
“…This network has been operating for over 10 years and has amassed tens of millions of images. As demonstrated by Grono et al (2017), it can be extrapolated from Jones et al (2011) that on the order of 10 % of THEMIS ASI images contain pulsating aurora.…”
Section: Instrumentation and Datamentioning
confidence: 96%
See 2 more Smart Citations
“…This network has been operating for over 10 years and has amassed tens of millions of images. As demonstrated by Grono et al (2017), it can be extrapolated from Jones et al (2011) that on the order of 10 % of THEMIS ASI images contain pulsating aurora.…”
Section: Instrumentation and Datamentioning
confidence: 96%
“…Pulsating auroral patches appear to be controlled by structures in the near-equatorial cold plasma (Rae, 2014) whose motion is almost entirely determined by E ×B drifting. Consequently, these patches appear to move with ionospheric convection and could be used to create automatically generated two-dimensional maps of convection (Yang et al, 2015;Grono et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsating auroras are a type of diffuse aurora characterized by quasi-periodic pulsations and precipitating electron energies between a few kiloelectron volts and hundreds of kiloelectron volts (Johnstone, 1978). They generally have an irregular, patchy structure (Royrvik and Davis, 1977) which constantly evolves in time (Shiokawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The THEMIS ASIs image the aurora in "white light" at a 3 second cadence on a 256 × 256 pixel CCD and have been operating continually for over 10 years to amass tens of millions of images. Following observations of Jones et al (2011), it can be surmised that pulsating aurora has been observed within on the order 10 % of these images (Grono et al, 2017).…”
Section: Reliability Of Cross-correlating Chorus Power With Auroral Bmentioning
confidence: 98%